Shaping Ability of the Root Canal System Using Reciproc and Reciproc Blue in Preparation of Artificial Canals - Hawazin Majdi; Khalid Merdad; Tariq Abuhaimed; Lujain Mirdad; Omar Alkhattab; Abdulaziz Bakhsh (Pesquisa Brasileira em Odontopediatria e Clínica Integrada)
Objective: To evaluate the effect of repeated usage of Reciproc and Reciproc Blue on their shaping ability and to determine the maximum number of artificial canals that they can prepare until fracture. Material and Methods: The two file systems, Reciproc and Reciproc Blue, were used to instrument a total of 436 resin blocks. The blocks simulated standardized root canals with a 35° angle of curvature. The rotary systems were divided into two groups (n=21). All canals were prepared to an apical size of 25 according to the manufacturer's instructions. A computer imaging program was then used to analyze canal straightening after pre- and post-instrumentation digital photography was superimposed. Results: Both Reciproc and Reciproc Blue instruments respected the original canal curvature. There were no significant differences between the instruments in terms of maintaining canal curvatures. Moreover, there were no significant differences in preparation time and the number of canals prepared before failure between the two instruments. Conclusion: Reciproc and Reciproc Blue were safe to use under the conditions of this study. Reciprocal motion files with or without heat treatment had comparable preparation time, shaping abilities, and the ability to maintain root canal curvatures.